2017
DOI: 10.1093/humrep/dex365
|View full text |Cite
|
Sign up to set email alerts
|

Human-specific subcellular compartmentalization of P-element induced wimpy testis-like (PIWIL) granules during germ cell development and spermatogenesis

Abstract: STUDY QUESTIONWhat is the dynamics of expression of P-element induced wimpy testis-like (PIWIL) proteins in the germline during human fetal development and spermatogenesis?SUMMARY ANSWERPIWIL1, PIWIL2, PIWIL3 and PIWIL4 were expressed in a sex-specific fashion in human germ cells (GC) during development and adulthood. PIWILs showed a mutually exclusive pattern of subcellular localization. PIWILs were present in the intermitochondrial cement and a single large granule in meiotic GC and their expression was diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 49 publications
4
48
0
Order By: Relevance
“…Our study provides the most comprehensive characterization of the PIWI-piRNA pathway in the human fetal testis to date. In addition to confirming and expanding upon the reported expression of HILI and HIWI2 (Gomes Fernandes et al 2018), we observed dynamic cytoplasmic to nucler localization of HIWI2 between GW18 -21 (Figure 1). Recent studies in human fetal ovary and adult testis showed that piRNAs were derived from genomic piRNA clusters (Ha et al 2014;Roovers et al 2015;Williams et al 2015).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study provides the most comprehensive characterization of the PIWI-piRNA pathway in the human fetal testis to date. In addition to confirming and expanding upon the reported expression of HILI and HIWI2 (Gomes Fernandes et al 2018), we observed dynamic cytoplasmic to nucler localization of HIWI2 between GW18 -21 (Figure 1). Recent studies in human fetal ovary and adult testis showed that piRNAs were derived from genomic piRNA clusters (Ha et al 2014;Roovers et al 2015;Williams et al 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Initially low levels of HILI at GW 11 increased through development, and protein was distributed throughout the cytoplasm as well as in puncta beginning at GW13, consistent with reported localization of MILI to pi-bodies, or intermitochondrial cement, in mice ). HIWI (PIWIL1) expression was not observed in fetal testes (Figure S1B), as expected based on its known adult-specific expression in human (Gomes Fernandes et al 2018) and mouse (Deng and Lin 2002) (Figure S1C). HIWI2…”
Section: Dynamic Expression and Subcellular Localization Of Piwi Homosupporting
confidence: 81%
See 1 more Smart Citation
“…Since the subcellular localization of a protein often dictates the mode of action and accessibility to substrates and cofactors, we sought to trace the intracellular distribution of PIWIL3 over developmental stages, to further elucidate the functional role of PIWIL3. While the intracellular distributions of PIWIL1, PIWIL2 and PIWIL4 have been elucidated in mouse testis 10,15 and human fetal oocytes 14 , the subcellular compartment(s) in which PIWIL3 exerts its function remains uninvestigated to date. Herein, we follow the distribution and expression pattern of PIWIL3 in bovine oocytes and preimplantation embryos, by transiently expressing EGFP-PIWIL3 fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to imply that products of Piwi genes (homologues of human PIWIL1, PIWIL2, PIWIL4 ) are not critically needed during oogenesis, maturation and post-fertilisation, at least in the murine system. We have previously established that human, macaque and bovine oocytes express large amounts of piRNAs, and 30-50% of these are enriched for transposon sequences, in particular, the expression of a fourth PIWI gene, PIWIL3 , was detected in human and bovine species but absent in murine systems 13,14 . Due, in part, to the perennial shortage of PIWIL3-specific antibodies, and the lack of mammalian species expressing PIWIL3 that are amenable to genetic manipulations, little is known about the function and subcellular localization of PIWIL3 as well as biogenesis in PIWIL3 related piRNAs.…”
Section: Introductionmentioning
confidence: 99%